Liquidity effects of COVID-19 in the European tourism industry - Gofran, Ruhana Zareen; Liasidou, Sotiroula; Gregoriou, Andros (My University, 2022)
We examine the influence of COVID-19 on liquidity of the tourism industry in the UK, Europe and Spain. In the short run, the pandemic causes significant negative stock market reaction in the tourism industry. In the long run, the tourism industry recovers from the fall in returns due to the pandemic. Liquidity significantly decreases due to COVID-19, for the UK, European and Spanish tourism markets, even when we encapsulate the influence of stock prices, trading volume and volatility. Our findings suggest that European equity markets have declined in efficiency due to the pandemic in the tourism industry. Our empirical analysis has important implications for policy makers. Tourism recovery strategies from the pandemic are required with immediate effect in order to restore the valuation of the tourism companies, given that the negative stock price reaction and lack of liquidity significantly reduces market value of the tourism firms across Europe. In order for the tourism industry to fully recover from COVID-19, investors need to have the confidence to buy large volumes of tourism company stocks, which will increase the price and liquidity, leading to a substantial increase in market capitalization.
Keywords: Liquidity; Tourism; European Market; COVID-19; Europe; Spain; UK